Faces of depression. Why do we need Batman, Joker, and Bane? - Simona Reghintovschi; Anatol Eduard Reghintovschi (Frontiers in Psychology)
Since 1939, when they first appeared in comic books, Batman and his antagonists have fascinated spectators with their endless drama. How can we understand the longevity of these characters in popular culture and the enthusiasm of the audience? Using a qualitative methodology informed by object relations theory and film analysis, the authors indicate that the drama enfolding on the cinema screen mirrors the depressive dynamics taking place in the inner word of the viewer who, by watching the movie, can master or, at least, keep at bay the terrifying conflicts between fragments of his ego represented by Batman, Joker, and Bane. In Gotham City, like in everyone's inner personality, the human conflicts related to dependency, loss, mourning, and change are always present.